Matriz de priorización como herramienta estratégica para el cumplimiento normativo de infraestructura y equipamiento en hospitales - González Campos, Edgar; Rosas Pacheco, Luis Antonio; Vega González, Arturo (Memorias del Congreso Nacional de Ingeniería Biomédica, 2021)
A prioritization matrix is presented as a proposal for an strategic management tool. It is intended to help in the detection of priority spotlights of non-conformities detected in equipment and infrastructure standards assessment for hospitals, all based on Mexican official normativity. It considers a multivariable analysis of risk for the establishment, professionals and patients, difficulty to solve, and financial costs. The methodology to build the matrix and the summatory formula are explained. Finally, a use example in a second level private hospital is presented as well.